Application Of Probability Theory In Practical Problems And Its Teaching Methodology - Nurmuxamedova Umida Baxtiyar Qizi (Peerian Journals Publishing, 2025)
This scientific paper analyzes the application of probability theory in practical problems and its teaching methodology. The study highlights the fundamental concepts of probability, theoretical foundations, and methods of applying them to real-life situations. Furthermore, it explores effective teaching strategies, including interactive and practical approaches, to simplify complex concepts for students. The results provide scientific and practical recommendations for teaching probability theory effectively
Keywords: probability theory; practical problems; teaching methodology